Elevated HbA1c in donor organs from patients without a diagnosis of diabetes portends worse liver allograft survival. Issue 9 (21st July 2017) - Ezekian, Brian; Mulvihill, Michael S.; Freischlag, Kyle; Yerokun, Babatunde A.; Davis, Robert P.; Hartwig, Matthew G.; Knechtle, Stuart J.; Barbas, Andrew S.
Abstract: Recipients of liver allografts from diabetic donors have decreased graft survival. However, limited data exist on the effects of donor HbA1c. We hypothesized that allografts from nondiabetic donors with elevated HbA1c would be associated with decreased survival. Liver transplant recipients from the UNOS database from nondiabetic donors were stratified into two groups: euglycemic (HbA1c<6.5) and hyperglycemic (HbA1c≥6.5). Propensity score matching (10:1) was used to adjust for donor and recipient characteristics. Kaplan‐Meier analysis was used to assess survival. Donors of hyperglycemic allografts were older (49 vs 36, P <.001), were more likely to be non‐white, had a higher BMI (29.8 vs 26.2, P <.001), were more likely to engage in heavy cigarette use (1.5% vs 1.3%, P =.004), had higher serum creatinine levels (1.3 vs 1.0, P =.002), and were more likely to be an expanded‐criteria donor (35.8% vs 14.4%, P <.001). After propensity matching to account for these differences, allograft survival was significantly decreased in the recipients of hyperglycemic allografts ( P =.049), and patient survival showed a trend toward reduction ( P =.082). These findings suggest that HbA1c may be a simple and inexpensive test with potential utility for better organ risk stratification.